(3JgPjH GdQjGSI hJQJjH GdSjGSIs - (3CHh YHO Gddg eMeO Hf Ydj Hf CHj Ydj GdbdYjs
(3ChdgG (B:s
(3GdMeO ddg MeOkG cKjQkG OGFekG , eJhGJQkG eJhGUdkG eJQGOakG eJcGJakG MeO ef EYJQa HHQg hBdGFg TGcQkG s
(3BNQgG (B:s
(3hbGd TQafi jG SjOi HbHhdg efi , abGd (B: (3EPgH HeJGYc jG GHf Ye , aEfG Cgd HjJ dG jbH dYi GdeYQha ecGaCI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdhQbI GdChdi efgG HNW eZGjQs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN CMeO Hf eMeO GdSGdei GdNGUI HR HjO s
Keywords: (3GdSjGSI hGdGLJeGYs